#### Answer

$\sqrt[6] (y^{5})$

#### Work Step by Step

$\sqrt y\sqrt[3] y=y^{1/2}y^{1/3}=y^{1/2+1/3}=y^{5/6}=\sqrt[6] (y^{5})$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\sqrt[6] (y^{5})$

$\sqrt y\sqrt[3] y=y^{1/2}y^{1/3}=y^{1/2+1/3}=y^{5/6}=\sqrt[6] (y^{5})$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.